Real-time monitoring of transcription with fluorescent light-up aptamers - Puro, Oskari (My University, 2023)
All living species rely on transcription to express their genes and consequently their specific traits. Transcription is the synthesis of RNA from a DNA template, and it is carried out by an enzyme known as RNA polymerase (RNAP). Transcription can be divided into three main stages: initiation, elongation, and termination. So, far commonly used in vitro transcription methods are laborious and there aren’t straightforward ways for monitoring the entire transcription cycle. In this study we used a fluorescent light-up aptamer (FLAP) to develop assay for real-time monitoring of transcription. We prepared several plasmids encoding the FLAP positioned at varied distances from a strong bacterial promoter and evaluated their suitability for monitoring various stages of transcription cycle with Escherichia coli RNAP. We optimized reaction component concentrations including Mg2+, NTPs, fluorophore, plasmid, and holoenzyme and additionally pH for further investigations with Spirochaeta africana transcription system. Following the optimization assays, we investigated the mostly unknown transcription factors from S. africana with the optimized assay. The elongation factor, LoaP, apparently slows down transcription elongation, but steadily increases the transcription output in long-term. The elongation factor, NusA, and the termination factor, Rho, had strong negative effects on transcription similarly to their well-studied E. coli counterparts. We discovered that the unique spirochetal Gre factor apparently facilitates transcription by having a strong positive effect on transcription initiation. The effect of GreA was studied with truncated S. africana Gre proteins that did not exhibit the same effect than full-sized GreA. Studies with S. africana transcription factors will help understanding transcription in pathogenic spirochetes which cause diseases such as Lyme disease, syphilis and leptospirosis. Results of this study validate that FLAP assays are a novel, straightforward way of monitoring transcription in real-time.
Keywords: fluorescent light-up aptamer, transcription, RNAP, transcription regulation, spirochetes